The Development and Application of Reverse Transcription Loop-Mediated Isothermal Amplification for The Diagnosis of Infectious Myonecrosis Virus in the White Shrimp (Litopenaeus vannamei) - Zakiah Widowati; Firma Firma; Dita Rustian; M. Tony Wartono Silaban; Freddy Riatmo; Sulistia Trikora Astuti; Nurlaila Nurlaila; Asep Dadang Koswara; Hastari Wuryastuti (Jurnal Sain Veteriner, 2012)
Infectious myonecrosis virus (IMNV) is one of the shrimp viral diseases caused by a double-stranded RNA virus, non-enveloped, and belongs to the family group Totiviridae. Weakness diagnosis of RNA viral diseases due to the RNA viruses are unstable and highly reactive. So far the diagnostic methods for detecting IMNV  with high accuracy is based on biomolecular test, such as reverse transcription polymerase chain reaction (RT-PCR). The RT PCR generally requires 4-8 hours of testing time, and also requires thermal cycler with a commercial kit materials which is relatively expensive. The purpose of the present study is to find and determine an alternative isolation of RNA from the samples and to determine whether the reverse transcription loop-mediated isothermal amplification (RT-LAMP) method based on biomolecular approach  can be an alternative testing method for diagnosis of IMNV in the white shrimps(L.vannamei).The RT-LAMP is more simple, straightforward, but it has a high sensitivity. Direct and indirect RNA extraction methods from samples and FTA cards give good results as a template in RT-PCR and RT-LAMP IMNV. The FTA card as one of the RNA samples of  storage media provides an alternative storage method that is easy, simple and has a shelf life of RNA in the long term (up to 6 months). Incubation time of RT-LAMP IMNV at 400C is between 15-30 minutes. Amplification time of RT-LAMP IMNV at 56o C is between 70-110 minutes. In the present study, the white shrimps (L.vannamei) that are positive IMNV-RT-LAMP provides 100% compliance results when tested by the RT-PCR method. The time of RT-LAMP amplification IMNV ranged from 70-110 minutes shorter than that of conventional PCR (180-240 minutes). Overall the RT-LAMP method for  IMNV can be applied as a method of testing for confirmative IMNV diagnosis in the white shrimps (L.vannamei). Keywords: IMNV, RT-LAMP, RNA, FTA cards,  white shrimp (L. Vannamei)